공기압을 이용한 패드 변압기 침수방지용 장치 개발에 관한 연구 - 김기현(Gi-Hyun Kim); 이상익(Sang-Ick Lee); 배석명(Seok-Myung Bae); 정찬웅(Chan-Oong Jung); 이재용(Jae-Yong Lee) (전기학회 논문지 P권, 58(1), 2009)
The inundation of substation and ground power equipment breaks out every summer season in low-lying downtown and low-lying shore by localized heavy rain, typhoon and tidal wave. For diminishing flood damage of electrical equipment in the root, flood protection system which is used the basic frame of Pad transformer is developed using pneumatic pressure. This system is established on pressure generator equipment and sensor of flooded level operates at flooding occurrence and is maintained a shutting tightly structure. The system is able to protect indraft water in Pad Transformer and supply the electricity at emergency(flooding). And we tested safety for insulation resistance at flooding and applying an electrical current. We estimate that loss cost which is caused by with flooding and the power failure will be diminished if it is addition to advances the reliability evaluation by setting an example.